Assessment of Surface Water Quality using Multivariate Statistical Analysis Techniques: A Case Study from Tahtali Dam, Turkey - YEREL, SUHEYLA (Asian Journal of Chemistry, 2010)
In this paper, the surface water quality of the Tahtali dam and tributaries in Izmir, Turkey are assessed by using multivariate statistical analysis techniques known as cluster analysis (CA), factor analysis (FA) and principal component analysis (PCA). Multivariate statistical analysis techniques were applied to the physical and inorganic chemical parameters including Cl–, NO3–, NH4+–N, oxygen saturation, colour, Na+, SO42-, total phosphorus, dissolved oxygen, BOD5 and COD obtained from the seven different surface water quality observation stations. These analyses results represent that domestic waste and nutrient pollution caused differences in terms of water quality in the northwest part of the area. Thus, this study show that the usefulness of multivariate statistical analysis techniques for analysis and interpretation in the water quality problem.